Social Support for Health Promotion of Elderly According to Local Wisdom and Policy Recommendation in Suthep Sub - District Municipality Muang Chiangmai District, Chiangmai Province - Jaitae, Samart; Sukseetong, Nuttron; Nummisri, Nammin (Humanities and Social Sciences Journal of Pibulsongkram Rajabhat University, 2022)
The purposes of mixed methods research aim to scribe the model local wisdom, social support with local wisdom for elderly health promotion and policy recommendation on local wisdom for health promotion of the elderly.The subjects cognized the elderly from 265 households and 24 stakeholders were participated. Data were collected using questionnaires, Informal interview and focus group discussion. Data were analyzed using descriptive statistics and content analysis. The results indicated that the Lanna rituals were the mental and social health promotion model. The social support of elderly according to local wisdom were on modulate level (= 2.17). In these regards, the stakeholders have suggested about the policy recommendation of social support in promoting the health of the elderly by local wisdom. In which, the related learning resources, communication processes in the community and public space developing for elderly health promotion.